2004
DOI: 10.1007/s00170-003-1576-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of optical glass machining

Abstract: Owing to brittleness and hardness, optical glass is one of the materials that is most difficult to cut. Nevertheless, as the threshold value of the undeformed chip thickness is reached, brittle materials undergo a transition from the brittle to the ductile machining region. Below this threshold, it is believed that the energy required to propagate cracks is larger than the energy required for plastic deformation. Thus, plastic deformation is the predominant mechanism of material removal in machining these mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 15 publications
0
17
0
2
Order By: Relevance
“…According to this model, BK7 glass can be grinded in the ductile mode as long as the depth of cut was smaller than a critical value, which was consistent with the wellknown ductile-regime grinding of brittle material [9]. Fang and Zhang [10] further studied the transition between brittle mode and ductile mode of BK7 glass by doing nano-indentation experiments. They stated that when undeformed chip thickness was very small, plowing and sliding were the major actions.…”
Section: Introductionmentioning
confidence: 93%
“…According to this model, BK7 glass can be grinded in the ductile mode as long as the depth of cut was smaller than a critical value, which was consistent with the wellknown ductile-regime grinding of brittle material [9]. Fang and Zhang [10] further studied the transition between brittle mode and ductile mode of BK7 glass by doing nano-indentation experiments. They stated that when undeformed chip thickness was very small, plowing and sliding were the major actions.…”
Section: Introductionmentioning
confidence: 93%
“…유리는 취성재료로서 크랙 전파가 임의의 방향으로 진행되어 유 리의 절단기술은 매우 흥미로운 주제다 [1] . 이 유리절단 방법에는 다이아몬드툴 같은 공구를 사용하는 기계적인 방법 [4][5][6] , 워터젯을 이용한 방법 [7,8] , 화학 에칭방법 [9,10] 그리고 레이저를 이용한 레이 저 절단방법 등이 있다 [11][12][13][14][15][16][17][18][19] . 현재 상용화된 방법은 기계적 절단 방법으로 절단날을 사용하는 연삭절단 방법과 다이아몬드 스크라 이빙 휠을 이용한 굽힘절단 방법이 있다 [20] .…”
Section: 서 론unclassified
“…Puttick et al [11] performed grooving test on soda-lime glass by a diamond tool and reported that below a critical depth of the cut predicted in order of magnitude by a fracture mechanics analysis, the material is removed by the action of plastic flow, leaving crack-free surfaces. Fang and Zhang [12] reported that below a certain threshold defined by undeformed chip thickness, it is believed that the energy required to propagate cracks is larger than the energy required for plastic deformation and hence the plastic deformation is the predominant mechanism of material removal below this threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Ductile machining of glass has mostly been performed with diamond cutting tool. Hence, one of the most critical issues in ductile mode machining has been the high cost of diamond tool due to severe tool wear [12]. This study has utilized superfine grain carbide endmill for machining of glass.…”
Section: Introductionmentioning
confidence: 99%